2019
DOI: 10.1002/ange.201911952
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazide‐Catalyzed Polyene Cyclization: Asymmetric Organocatalytic Synthesis of cis‐Decalins

Abstract: Polyene cyclizations offer rapid entry into terpenoid ring systems. Although enantioselective cyclizations of (E)‐polyenes to form trans‐decalin ring systems are well precedented, highly enantioselective cyclizations of (Z)‐polyenes to form the corresponding cis‐decalins have not been reported. Here, we describe the first application of iminium catalysis to the initiation of polyene cyclizations. Ethyl 1,2‐diazepane‐1‐carboxylate catalyzes the cyclization of polyenes bearing enal initiators. Moreover, chiral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless,all attempts along this line met with diminished yields and enantioselectivities until very recently,the Gleason group described the asymmetric formation of cis-decalin 14 from (Z)-polyene substrate (13)t hrough iminium ion catalyzed polyene cyclization (Scheme 2b). [12] Although great progress has been made,alternative methods are still demanding partly because elaborations of the phenyl group to other functional species are challenging and require harsh conditions.Eschenmoser disclosed that enantiomerically enriched 15 could be converted into racemic trans-decalin 16 under thermodynamic control (Scheme 2c). It was presumed isomerization of the exocyclicd ouble bond of 15 to tetrasubstituted alkene occurred at first, thus eliminating the stereochemical information, prior to diastereospecific carbocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless,all attempts along this line met with diminished yields and enantioselectivities until very recently,the Gleason group described the asymmetric formation of cis-decalin 14 from (Z)-polyene substrate (13)t hrough iminium ion catalyzed polyene cyclization (Scheme 2b). [12] Although great progress has been made,alternative methods are still demanding partly because elaborations of the phenyl group to other functional species are challenging and require harsh conditions.Eschenmoser disclosed that enantiomerically enriched 15 could be converted into racemic trans-decalin 16 under thermodynamic control (Scheme 2c). It was presumed isomerization of the exocyclicd ouble bond of 15 to tetrasubstituted alkene occurred at first, thus eliminating the stereochemical information, prior to diastereospecific carbocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, one-step catalytic asymmetric methods have been achieved. In 2020, Gleason et al 10 reported a highly enantioselective synthesis of a series of cis-fused octahydrophenanthrenes bearing a methylated quaternary stereocenter by chiral bicyclic hydrazide-catalyzed asymmetric polyene cyclization of Zpolynenes (Figure 1b). Subsequently, by employing an elegant rhodium-catalyzed asymmetric intramolecular carboacylation of olefins with benzocyclobutanones, 11 Dong et al 8c achieved the enantioselective construction of cis-fused octahydrophenanthrene ring systems in one step and completed the first total synthesis of (−)-thebainone (Figure 1b).…”
mentioning
confidence: 99%